2022
DOI: 10.1021/acs.biochem.1c00705
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metals Induce Quenching of Monomeric Near-Infrared Fluorescent Proteins

Abstract: Transition metals such as zinc and copper are essential in numerous life processes, and both deficiency and toxic overload of these metals are associated with various diseases. Fluorescent metal sensors are powerful tools for studying the roles of metal ions in the physiology and pathology of biological systems. Green fluorescent protein (GFP) and its derivatives are highly utilized for protein-based sensor design, but application to anaerobic systems is limited because these proteins require oxygen to become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 80 publications
(141 reference statements)
1
16
0
Order By: Relevance
“…Similarly, subnanomolar dissociation constants of Cu 2+ were found for CreiLOV C17A and CreiLOV N41D (Tables and S4, Figure S11). These results are similar to those that we recently reported for Cu 2+ quenching of near-infrared fluorescent proteins, where a picomolar Cu 2+ K d was determined with nitrilotriacetic acid (NTA) present, but micromolar K d values were found using the direct titration method …”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, subnanomolar dissociation constants of Cu 2+ were found for CreiLOV C17A and CreiLOV N41D (Tables and S4, Figure S11). These results are similar to those that we recently reported for Cu 2+ quenching of near-infrared fluorescent proteins, where a picomolar Cu 2+ K d was determined with nitrilotriacetic acid (NTA) present, but micromolar K d values were found using the direct titration method …”
Section: Resultssupporting
confidence: 91%
“…Previous work found that the FbFP iLOV can be quenched by Cu 2+ (apparent dissociation constant, K d = 4.72 μM at pH 7.4) and other FbFP mutants are sensitive to Hg 2+ and As 3+ ions, although none of these FbFPs were tested in live cells. Our group found that Cu 2+ induces quenching of CreiLOV with a slightly stronger binding affinity ( K d = 3.2 ± 0.3 μM) than iLOV and can detect excess Cu 2+ ions added to Escherichia coli cells . Both iLOV and CreiLOV dissociation constants were obtained by direct titration with Cu 2+ , an approach that we have since shown is not suitable for this metal under neutral buffered conditions and can underestimate the affinity . A copper binding site was proposed within the FMN binding pocket. , In CreiLOV, copper may coordinate with Cys17 and Asn41 (Figures A,B and S1), and in iLOV, these residues are Asn17 and Asn41.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…As a possibility, the substitution of Asn by Tyr at position 15 in miniGFPs improved copper ion coordination, however, elucidation of the exact mechanism of Cu-sensitivity requires further functional and structural studies. The calculated K d ’s for miniGFPs were comparable to one of the most sensitive Cu(II) biosensors engineered based on EGFP (16 nM for EGFP-based biosensor vs. 67–68 nM for miniGFPs) ( Bálint et al, 2013 ), while the highest affinity to Cu(II) among all FPs was recently discovered in biliverdin binding protein miRFP670 reaching picomolar range ( Zhao and Zastrow, 2022 ). From another hand, there was no literature data on flavin binding FP sensitivity to Cu(I), which represents more physiologically relevant form of copper in eukaryotic cells.…”
Section: Discussionmentioning
confidence: 72%